Feeding practices of under-two children in Ethiopia: A systematic review and meta-analysis - Sisay Eshete Tadesse; Amare Tariku; Tefera Belachew (PLoS ONE, 2026)
Background Globally, child feeding practices remain suboptimal and contribute substantially to a high burden of malnutrition. In Ethiopia, evidence on the overall status of feeding practices among children under two years of age is limited. This study therefore sought to estimate the pooled prevalence of timely initiation of breastfeeding, exclusive breastfeeding, timely initiation of complementary feeding, and minimum acceptable diet, as well as to identify the factors associated with these practices. Method This systematic review and meta-analysis was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines. A comprehensive literature search was performed in Scopus, HINARI, the Cochrane Library, and PubMed/MEDLINE. Cross-sectional and case-control studies published in English were included. Study quality was assessed using the Joanna Briggs Institute critical appraisal checklist. Heterogeneity across studies was assessed using Cochran Q test and the I 2 statistic. Data analysis was done using STATA/MP version 17.0. Adjusted odds ratios with 95% confidence intervals were used to identify factors. Publication bias was assessed using funnel plots, Egger weighted regression, and Begg rank correlation tests. Results A total of 107 articles were included in this study. The pooled prevalence of timely initiation of breastfeeding, exclusive breastfeeding, timely initiation of complementary feeding, and optimal feeding practice were 64% (95% CI: 50%, 78%), 58.6% (95% CI: 52.6%, 64.5%), 60.51% (95% CI: 54.2%, 66.9%), and 20.4% (95% CI: 13.6%, 27.0%), respectively. Antenatal care (AOR = 3.4; 95% CI: 1.5, 7.5), place of delivery (AOR = 2.3; 95% CI: 1.1, 4.9), and normal delivery (AOR = 3.3; 95% CI: 1.1, 10) were positively associated with timely initiation of breastfeeding. Exclusive breastfeeding was positively associated with infant age 0–1 (AOR = 4.4; 95% CI: 1.4, 13.6) and 2–3 months (AOR = 2.5; 95% CI: 1.2, 5.1), maternal age > 35 (AOR = 3.4; 95% CI: 1.3, 8.7), residence (AOR = 1.8; 95% CI: 1.1, 3.1), maternal occupation (AOR = 1.8; 95% CI: 1.2, 2.7), place of delivery (AOR = 2.1; 95% CI:1.2, 3.7), normal delivery (AOR = 1.7; 95 CI:1.2, 2.6), postnatal care (AOR = 2.3; 95% CI: 1.2, 4.3), counseling (AOR = 2.3; 95% CI:1.4, 3.9) and husband support (AOR = 2.9; 95% CI:1.9, 4.4) were positively associated with EBF. Antenatal care (AOR = 3.4; 95% CI:1.5, 7.5) and place of delivery (AOR = 2.3; 95% CI:1.1, 4.9) were positively associated with timely initiation of complementary feeding. Optimal infant feeding practice was positively associated with nutrition education through demonstrations (AOR = 2.1; 95% CI:1.3, 3.3) and age of child 18–23 months (AOR = 2.7; 95% CI:1.2, 6.1). Conclusion This study demonstrated that infant feeding practices were below both national and international recommendations, exposing children at higher risk of malnutrition, morbidity, and mortality. These suboptimal feeding practices also hinder progress toward achieving to achieving the Sustainable Development Goals. Several factors were identified as significant determinants of feeding practices, including antenatal care attendance, place and mode of delivery, postnatal care utilization, maternal occupation, maternal age, child’s age, breastfeeding counseling, husband’s support, place of residence, and participation in complementary food preparation demonstrations. Improving infant feeding practices therefore requires a comprehensive approach. Key strategies to improve infant feeding practices should include nutrition education through practical demonstrations, promoting full attendance of antenatal and postnatal care, increasing institutional deliveries, enhancing husband involvement, and tailoring interventions to the child’s age as well as the mother’s age and place of residence.